The analysis of structure and strength of c-o bond in copper (ii) benzoate and its derivatives by ftir spectroscopy / Zuraida Khusaimi and Norbani Abdullah - Khusaimi, Zuraida; Abdullah, Norbani (2002)
Copper (ll) benzoate and its derivatives namely copper (II) 4-flourobenzoate, copper (II) 4-chlorobenzote were prepared by refluxing copper (II) monohydrate with the corresponding acids. The material studied are potential low-dimensional, thermally stable molecular electronics. The structure and strength of respective C-O bond of the ligand of these samples are investigated by Fourier Transform Infrared Spectroscopy (FTIR). Copper (ll) 4-flourobenzoate and copper (II) 4-chlorobenzoate are electron-attracting substituents and have lower c-o bond strength than copper (II) benzoate, and thus stronger bridging bond between the ligand and the copper(IJ) ion. The order of the strength of the bridging bond is as follows: